New record of River Otter (Lontra longicaudis Olfers, 1818) in the Extreme South of Yungas of Northwestern Argentina - Albanesi, Sebastian Alejandro (2017)
The neotropical river otter (Lontra longicaudis) has scarce distribution records in Northwestern Argentina (NWA); most of them are old, inaccurate, and/or coming from mentions not well corroborated. We report filmic and photographic records of this species from the piedemont of Yungas of the southern NWA obtained in riparian forest patches located in citrus farms in Tucumán province. The record is important by the scarcity of information, but also because this otter have its southernmost distribution in the western portion in this area, it is a taxa with conservation concerns, and the records come from a natural environment heavily modified.